Hemispherical array of sensors with contractively wrapped polymer petals for flow sensing. (3rd October 2017) - Kanhere, Elgar; Wang, Nan; Kottapalli, Ajay Giri Prakash; Miao, Jianmin; Triantafyllou, Michael
Abstract: Hemispherical arrays have inherent advantages that allow simultaneous detection of flow speed and direction due to their shape. Though MEMS technology has progressed leaps and bounds, fabrication of array of sensors on a hemispherical surface is still a challenge. In this work, a novel approach of constructing hemispherical array is presented which employs a technique of contractively wrapping a hemispherical surface with flexible liquid crystal polymer petals. This approach also leverages the offerings from rapid prototyping technology and established standard MEMS fabrication processes. Hemispherical arrays of piezoresistive sensors are constructed with two types of petal wrappings, 4-petals and 8-petals, on a dome. The flow sensing and direction detection abilities of the dome are evaluated through experiments in wind tunnel. Experimental results demonstrate that a dome equipped with a dense array of sensors can provide information pertaining to the stimulus, through visualization of output profile over the entire surface.